RETRACTED: Exploring Smartphone Use Patterns and Their Associations with Demographic Characteristics, Socio-psychological Well-being, and Socio-cultural Factors among Nigerian Youth - Akeusola, Bolanle (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
This article was retracted due to an unintentional case of double publication. The article was previously published in another journal with the DOI [https://doi.org/10.15282/ijhtc.v8i2.9692]. The duplication occurred as a result of miscommunication during the submission process, where the manuscript was submitted to multiple journals simultaneously without the knowledge of the authors and editorial teams. This retraction is issued to maintain the integrity of the scholarly record and adhere to the journal's publication ethics policies. The widespread adoption of smartphones has transformed communication and information access, particularly among Nigerian youths. As Africa’s most populous nation and rapidly digitizing economy, Nigeria offers a unique backdrop to investigate the complex interplay between smartphone use patterns, socio-psychological well-being, and socio-cultural factors among its youth population. This study employed a cross-sectional survey research design to explore these intricate relationships comprehensively. The methodological approach involved a quantitative research framework using a tailored measurement scale developed to gather relevant data, encompassing demographic details, smartphone use patterns, socio-psychological well-being indicators, and socio-cultural factors. This study focused on Nigerian youth aged 18 to 30 years, employing a snowball sampling technique to disseminate the research instrument through WhatsApp and Telegram platforms. A total of 1241 participants from different regions of the country were included in the study. The results showed significant variations in smartphone use patterns among Nigerian youth based on age groups, gender, and socioeconomic background. The results revealed significant variations in smartphone use patterns based on demographic characteristics, including age, sex, and socioeconomic background. Furthermore, smartphone use patterns exhibited significant correlations with various aspects of socio-psychological well-being, such as emotional well-being, stress levels, sleep quality, and life satisfaction. Sociocultural factors did not significantly predict smartphone use patterns; family dynamics and peer interactions emerged as significant indirect influencers through psychological well-being. The recommendations arising from the study’s findings suggest tailored interventions for demographic groups, promotion of digital well-being, and the incorporation of digital literacy education.